Fidelity Assessment of a Social Work–Led Intervention Among Patients With Firearm Injuries. (September 2020) - Lyons, Vivian H.; Benson, Lina R.; Griffin, Elizabeth; Floyd, Anthony S.; Kiche, Sharon W.; Haggerty, Kevin P.; Whiteside, Lauren; Conover, Sarah; Herman, Daniel B.; Rivara, Frederick P.; Rowhani-Rahbar, Ali
Purpose: To support future development and refinement of social work–led intervention programs among patients with firearm injuries and to demonstrate how a fidelity assessment can be used to adjust and refine intervention delivery in an ongoing trial. Method: We conducted a fidelity assessment of a randomized controlled trial of a social work–led intervention among patients with a firearm injury. Results: We found that our study intervention was well implemented, meeting 70% of the fidelity assessment score items, however, noted lower fidelity with client-based items. Discussion: As a result of fidelity assessment findings, we refined intervention delivery to improve implementation fidelity including beginning to review cases of all patients each month rather than focusing on patients in crisis. Our fidelity assessment process and findings offer insight into the challenges of implementing an intervention among patients with firearm injuries and highlight the value of monitoring intervention fidelity during an ongoing trial.